PSYCHOLOGICAL CHALLENGES OF THE DIGITAL TRANSFORMATION IN BULGARIAN EDUCATION – A THEORICAL MODEL - Kolenarova, Tanya (E-Journal VFU, 2025)
The study analyzes the psychological challenges arising from the digital transformation of education in Bulgaria. Based on a review of existing research, policies, and strategic documents, a theoretical model is developed to describe the interaction between technological innovations (including artificial intelligence), pedagogical practices, and the psychosocial effects on students and teachers. The analysis summarizes findings from national and international sources, including the National Strategy for the Digitalization of Education 2024–2030 (Ministry of Education and Science), the White Paper on Artificial Intelligence (European Commission, 2021), and AI and Education: Guidance for Policy-Makers (UNESCO, 2023). The model identifies major psychological risks—stress, burnout, digital dependency, and social isolation—and protective factors such as motivation, digital competence, and ethical frameworks. The goal is to outline a path toward the balanced and human-centered integration of technology in the Bulgarian educational system.